Impacts of the COVID-19 pandemic on violence against women: reflections from the theory of human motivation from Abraham Maslow - Santos, Luisa Souza Erthal (2020)
Introduction: The pandemic and social isolation scenario caused by the new Coronavirus (COVID-19) can directly affect the prevalence of domestic violence against women in Brazil. Objective: To reflect on the impacts of the COVID-19 pandemic on violence against women, through an analysis over the human motivation theory of Abraham Maslow. Method: This is a reflective study with documentary analysis carried out in June 2020, whose theoretical framework was Abraham Maslow's theory of basic human needs. Results: Hierarchical levels were described according to the Maslow pyramid and a parallel was drawn with data on violence against women before and during the COVID-19 pandemic period. Conclusion: The paths to services related to gender violence must be updated to reflect changes in available health services. The present study demonstrated that the COVID-19 pandemic can affect women who experience domestic violence at all hierarchical levels in the Maslow pyramid.